1999
DOI: 10.1007/s004310051098
|View full text |Cite
|
Sign up to set email alerts
|

Pro- and anti-inflammatory cytokine patterns during and after cardiac surgery in young children

Abstract: The downregulation of ex vivo pro- and, to some extent, anti-inflammatory cytokine production may be a reflection of a cellular stress response, induced by anaesthesia, cardiopulmonary bypass and surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 25 publications
0
27
0
2
Order By: Relevance
“…We observed expected changes in the pro and anti-inflammatory response after CPB 34 . We did not identify expected changes in claudin 3 concentrations in response to TNF-α and IFN-γ in our pilot population.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…We observed expected changes in the pro and anti-inflammatory response after CPB 34 . We did not identify expected changes in claudin 3 concentrations in response to TNF-α and IFN-γ in our pilot population.…”
Section: Resultsmentioning
confidence: 62%
“…It is possible that early loss of claudin 3 expression was prevented by a protective effect of post-CPB anti-inflammatory responses. Pro and anti-inflammatory cytokines may have opposing effects on the intestinal epithelial barrier and the balance of the response determines maintenance or loss of function 34,35 . For example, IL-6 in murine models promotes intestinal epithelial proliferation and healing and could be protective if elevated in the setting of ischemia-reperfusion injury, while IFN-γ is cytotoxic 6,35 .…”
Section: Resultsmentioning
confidence: 99%
“…The post-operative cytokine response in paediatric patients is different from that in adults [6]. Recent animal studies in piglets showed that CPB without cardiac surgery elicits a proas well as an anti-inflammatory cytokine response during the first 4 h after the procedure [2].…”
Section: Discussionmentioning
confidence: 98%
“…The induction of an inflammatory response with the release of cytokines, induction of leukocyte-endothelium interaction and generation of oxygen free radicals might be the major pathomechanism for the development of the microvascular perfusion injury. In clinical as well as in experimental studies, the relationship between CPB and the production of cytokines has been demonstrated [17,20]. The contact of blood and blood cells with foreign surfaces like bypass circuits and the mechanical stress induced by the pump mechanism (especially roller pumps) are major pre-requisites for the induction of cytokine release.…”
Section: Discussionmentioning
confidence: 99%